Pengaruh Disiplin Pegawai, Fasilitas Kerja, dan Kompetensi Pegawai Terhadap Kualitas Pelayanan (Business and Accounting Education Journal, 2022)
The purpose of this study was to analyze the effect of employee discipline, work facilities and employee competence on service quality at the Petungkriyono District office, Pekalongan Regency simultaneously or partially. The population in this study were all people in Petungkriyono District, Pekalongan Regency who had received services in Petungkriyono District, Pekalongan Regency. The sampling technique used iteration formula with 116 respondents. Data were collected by means of observation, interviews, questionnaires and documentation. The results of the study show: (1) there is a positive and significant influence between the variables of employee discipline, work facilities, and employee competence simultaneously on service quality at the Petungkriyono sub-district office of 57.7%, (2) there is a positive and significant effect of employee discipline on service quality, (3) there is a positive and significant effect of work facilities on service quality, (4) there is a positive and significant influence of employee competence on service quality.